Peran Tata Kelola Perusahaan dalam Mitigasi Risiko Keuangan The Role of Corporate Governance in Mitigating Financial Risk - Sabrina Dewi Hasna (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study discusses how corporate governance (Good Corporate Governance/GCG) plays a role in reducing and controlling financial risk in an organization. Financial risk is an inseparable aspect of business activities, especially when companies face unstable and challenging market conditions. Therefore, a governance system is needed that can help companies recognize potential risks early on, as well as set appropriate handling strategies to minimize their impact on business continuity. The method used in this study is a literature study, namely by collecting secondary data from scientific journals and trusted articles that are relevant to the topic. The discussion includes theoretical foundations related to GCG principles, corporate governance structures, and financial risk mitigation steps. In addition, the role of the government in providing regulatory support is also discussed as part of the external factors that affect the effectiveness of corporate governance. From the results of the analysis, it is known that the application of GCG principles such as transparency, accountability, and responsibility has a major influence on the company's resilience in facing financial risks. A clear organizational structure and strong supervision allow companies to manage risks systematically. In other words, GCG makes a real contribution to strengthening a sustainable and adaptive risk management system to changes in the business environment.